Labor Requirement and Costs for Harvesting Tomatoes - Zhengfei Guan; Feng Wu; Steven A. Sargent (EDIS)
Florida accounts for 30% to 40% of all commercially produced fresh-market tomatoes in the United States. Almost every southern county in the state grows tomatoes. This 4-page fact sheet written by Zhengfei Guan, Feng Wu, and Steven Sargent and published by the UF/IFAS Food and Resource Economics Department presents the results of a 2015 study that examined the time it takes to harvest this important crop. http://edis.ifas.ufl.edu/fe1026